Peroxiredoxin-Glutaredoxin and Catalase Promote Resistance of Nontypeable Haemophilus influenzae 86-028NP to Oxidants and Survival within Neutrophil Extracellular Traps - Juneau, Richard A. (Infect Immun, 2014)
Nontypeable Haemophilus influenzae (NTHI) is a common commensal and opportunistic pathogen of the human airways. For example, NTHI is a leading cause of otitis media and is the most common cause of airway infections associated with chronic obstructive pulmonary disease (COPD). These infections are often chronic/recurrent in nature and involve bacterial persistence within biofilm communities that are highly resistant to host clearance. Our previous work has shown that NTHI within biofilms has increased expression of factors associated with oxidative stress responses. The goal of this study was to define the roles of catalase (encoded by hktE) and a bifunctional peroxiredoxin-glutaredoxin (encoded by pdgX) in resistance of NTHI to oxidants and persistence in vivo. Isogenic NTHI strain 86-028NP mutants lacking hktE and pdgX had increased susceptibility to peroxide. Moreover, these strains had persistence defects in the chinchilla infection model for otitis media, as well as in a murine model for COPD. Additional work showed that pdgX and hktE were important determinants of NTHI survival within neutrophil extracellular traps (NETs), which we have shown to be an integral part of NTHI biofilms in vivo. Based on these data, we conclude that catalase and peroxiredoxin-glutaredoxin are determinants of bacterial persistence during chronic/recurrent NTHI infections that promote bacterial survival within NETs.